Exploring the Influences of Hegemonic and Complicit Masculinity on Lifestyle Risk Factors for Noncommunicable Diseases Among Adult Men in Maseru, Lesotho - Nkeka P. Tseole; Kerry Vermaak (American Journal of Men's Health, 2020)
Masculinity is an important health determinant and has been studied as a risk factor for communicable diseases in the African context. This paper explores how hegemonic and complicit masculinities influence the lifestyle risk factors for noncommunicable diseases among men. A qualitative research method was used, where eight focus group discussions were conducted among adult men in Maseru, Lesotho. The data were analyzed using a thematic analysis approach. Although the participants typically described taking responsibility as a key feature of what it meant to be a man in Lesotho, their reported behaviors and rationales indicated that men commonly abdicated responsibility for their health to women. Participants were aware of the negative effects of smoking on health and acknowledged the difficulty to stop smoking due to the addictive nature of the habit. The initiation of smoking was linked by participants to the need to be seen as a man, and then maintained as a way of distinguishing themselves from the feminine. Regarding harmful alcohol consumption, participants reported that stress, particularly in their relationships with women, were linked to the need to drink, as they reported limited outlets for emotional expression for men in Lesotho. On the subject of poor diet, the study found that most men were aware of the importance of vegetable consumption; the perceived lengthy preparation process meant they typically depended on women for such healthy food preparation. Almost all participants were aware of the increased susceptibility to diverse negative health effects from physical inactivity, but because of the physical nature of the work, those engaged in traditionally masculine occupations did not exercise. In the context of lifestyle risk factors for noncommunicable diseases, masculinity has positive and negative impacts. It is important to design health education programs targeting men to successfully mitigate the negative health impacts of masculinity.